Práticas integrativas e complementares no contexto gerontológico : a voz dos idosos - Frigotto, Diego Ferrari (2013)
Population aging in Brazil and the world was a great achievement of the twentieth century due to scientific advances, medical interventions, sanitation. The present study aimed to investigate the knowledge, use and acceptance of complementary and integrative therapies for the elderly in different contexts. The study used a qualitative approach, with character exploratory and descriptive and used the focus group method for collecting and analyzing data as postulates Gatti. With a sample of 78 elderly with three groups (GF) focal programs tied to universities open to seniors tied the University Without Limits Project of Universidade Regional Integrada do Alto Uruguai e das Missões - URI Campus Erechim, and the Center Regional Studies and Activities For Seniors (CREATI) on the Universidade de Passo Fundo and 4 GF linked to coexistence groups for the elderly in the context of Paim Filho and Maximiliano de Almeida. Data collection occurred in the second half of 2012 with three sessions in each GF, data were recorded and transcribed by the researcher. Part of the results was compiled in two scientific productions, both attached to this text. The first entitled "The knowledge and use of complementary and integrative practices by elders from different contexts" aimed to investigate what forms of complementary and integrative practices seniors in health care use. Thus, this study aims to investigate the knowledge and use of complementary and integrative practices by elders from different contexts. Outcome data analyzed a corpus compuserem detailed and reliable interpretation. In interactionist dimension and interpretation anchored in the frame built. To interpret and analyze the data we used the postulates of Gatti. This showed that the use and knowledge of complementary and integrative practices is vast among the elderly about all those not in countersignatures National Policy on Integrative and Complementary, the same feature are used as preventive and curative and are linked to family culture. The two scientific production entitled: "Women's open university for the elderly and health care: knowledge and use of medicinal plants and herbal therapy" aimed at identifying the knowledge and practice by older women, medicinal plants and herbal medicine. The analysis of data was similar to the one article. It was noted that elderly women have great knowledge in the use of medicinal plants, based on what this transmission knowledge through the generations, but this use and not referred to health professionals unlike herbal medicines whose use is prescribed by doctors. The research took place without difficulty, however, presents limitations because it is specific contexts can not be generalized. The results indicate the need for further studies in these contexts to a better knowledge of the forms of health care use by the elderly